Effects of the Ketogenic Diet on Metabolic Syndrome - Anderson, Michael E.; Tulp, Orien L (British Journal of Healthcare and Medical Research, 2023)
The global prevalence of obesity and metabolic syndrome and its pathophysiologic sequela are currently approaching epidemic proportions, with unacceptable levels in much of Westernized and economically developed society. The clinical stigmata of metabolic syndrome typically include the comorbidities of obesity, hypertension, non-insulin dependent diabetes, and hyperlipidemia with decreased plasma high density lipoprotein concentrations. In addition, a common finding of hyperinsulinemia and insulin resistance typical of high carbohydrate diets often accompanies the syndrome. The incorporation of the insulin sparing ketogenic diet as a dietary strategy for the treatment of metabolic syndrome may bring about improvements in insulin action and substrate utilization in peripheral tissues with at least a partial if not significant resolution of the syndrome. Thus, the ketogenic diet in addition to adaptations toward a healthy lifestyle and pharmacologic therapies have been explored as potential mechanisms to resolve the pathophysiologic sequela of obesity and metabolic syndrome and their impact on the delivery of healthcare. Metabolic syndrome (MetS) is a condition defined as a clustering of risk factors that is strongly associated with obesity, heart disease, and diabetes [22]. It has recently been estimated that the global prevalence of MetS has reached epidemic levels including the U.S.A., where it has been estimated that 20% to 25% of the adult global population meets the diagnostic criterion for MetS [3], which may be established when at least three of the five primary risk factors are present. The risk factors include a large waistline (abdominal or visceral obesity), high plasma triglyceride levels, low plasma HDL cholesterol concentrations, elevated blood pressure, and fasting hyperglycemia. The standard and most effective treatments for MetS to date have been incorporation of lifestyle changes, with dietary interventions being one of the major effective lifestyle modifications utilized to treat both obesity and MetS [14];[41]. The Ketogenic Diet (KD) is one dietary intervention that may have the potential to improve MetS risk factors. Historically, one of the primary uses of the KD has been to treat epilepsy, however, there is substantial evidence that it may also help to improve other conditions and illnesses, including obesity and MetS [30]; [48]; [35]. Despite this potential, certain dietary misconceptions may have prevented or slowed further research on the KD applications to weight control and use of the KD, particularly the emergence of the national dietary guidelines that have now promoted a low-fat, high-carbohydrate diet for several decades [18]; [51]; [52]. The purpose of this paper is to conduct a review of the literature regarding MetS, the KD, and the implications of the KD as a treatment for obesity and MetS. Existing research is systematically reviewed regarding the KD’s potential to address MetS and MetS risk factors. The results of the review indicate the validity of the diet and the need for further research on the KD and its potential to address the benefits, potential risks and clinical efficacy of the KD on reducing the pathophysiologic sequalae of obesity and MetS. MetS = Metabolic Syndrome, KD = ketogenic diet, KB = ketone bodies, including metabolic remnants acetoacetate (AcAc),3-beta-hydroxybutyrate (3HB), and acetone, PSMF = Protein Sparing Modified Fast, HDL, HDL-C= plasma high density cholesterol lipoprotein, LDL, LDL-C = low density cholesterol lipoprotein, TG, TRIG = plasma triglycerides, CRP = C-reactive protein, GLUT4 = Glucose Transporter 4, and insulin-linked cellular entity, ATP = Adenosine tri-phosphate, a high energy phosphate, CCK = cholecystokinin, CR = calorie restricted diet, LFD = low fat diet, LCKD = low calorie ketogenic diet, BP = blood pressure; SBP = systolic blood pressure; DBP = diastolic blood pressure, A(1c) = glycosylated hemoglobin fraction, NHLBI = National Heart, Lung and Blood Institute of the National Institutes of Health